Ultrasound of musculoskeletal soft tissue masses - Arun Kinare; Mugdha Brahmnalkar; Shalini D′Costa (Indian Journal of Radiology and Imaging, 2007)
Soft tissue masses have a varied presentation. Though all masses cannot be optimally imaged on USG, its easy availability, real-time capability, and cost-effectiveness, as well as the freedom it provides to examine in any direction, make it an automatic choice as a first-line modality. Though Doppler is an exciting modality, it has its limitations and is not always rewarding. USG is more useful for superficially located masses. The role of USG is to provide information about the extent of the mass, its nature, and its relationship to the surrounding structures. One important aim is to differentiate between a pseudotumor and a true mass lesion. Doppler can provide additional information in selected cases. USG can play a pivotal role in guiding a needle for obtaining a sample for tissue diagnosis. Benign lesions are more common than malignant ones, in day-to-day practice. As with any other musculoskeletal examination, technical expertise and a sound knowledge of musculoskeletal anatomy are important.